FEEDING MANAGEMENT PRACTICES OF DAIRY ANIMALS IN PATAN DISTRICT OF NORTH GUJARAT REGION - Patel, N.B; Patel, J.B; FULSOUNDAR, A. B.; Rao, T. K. S.; Modhi, R.J (Indian Journal of Animal Production and Management, 2017)
A field survey was conducted to collect the first hand information on dairy animal management practices followed by the dairy animal owners of Patan district of north Gujarat. Existing feeding management practices were studied through predesigned and pretested questionnaire from 100 dairy animal owners. As far as feeding of green fodder is concerned, leguminous and non leguminous fodders used by farmers were 76.00 & 24.00 percent respectively. About 23.00 per cent farmers used to feed merely compounded cattle feed, while 77.00 percent farmers used mixture of home-made concentrate with compounded feed. Concentrate feeding was significantly (P<0.01) different with land holding of farmers. Feeding of mineral mixture was significantly (P<0.01) different among the Talukas.